Histopathological Alteration and Molecular Detection of Gills Rot Fungus in Carp Fish - Al-Jumaa, Zahraa Mustafa; AL-Taee, Shahbaa Khalil; Jaber, Mohammed Tariq; Rahhawi, Aseel Mohammed (Journal of applied veterinary sciences, 2024)
Nowadays, diseases are a major concern in fish production, particularly in gills, which play a crucial role in blood oxygenation, acid-base balance, osmoregulation, and waste elimination. Fungal infections, particularly Branchiomyces, cause respiratory problems in fish. This study aims to determine the causative agent causing high mortality in common carp, Cyprinus carpio, in the middle Euphrates in Iraq. One hundred infected fish were sampled for microbial, histological, and molecular examination. Gill tissue was examined as well for histological alterations, and DNA was isolated from Branchiomyces and amplified with universal primers. Microscopically identifying Branchiomyces spp. using lactophenol staining, non-separated hyphae and spores (5–9 m in size) at various stages inside the structures of gill tissue were present. Histopathological examination revealed hyperplasia of epithelial cells and infusion of gill filaments, while primary gill filaments displayed severe hemorrhage and edema. Hyphae of Branchiomyces have been detected between necrotic and edematous myofiber. The ITS PCR products of the fungal isolate were found to be positive at 540 bp molecular weight. Economic losses can occur as a result of fish infections caused by Branchiomyces. Histopathological lesions in gill tissue indicated the presence of Branchiomyces infection, which was confirmed by molecular and microscopical examination.